ACADEMIC MOTIVATION LEVEL AND ATTITUDE TOWARDS SOCIAL STUDIES AMONG PUBLIC SCHOOL SECONDARY STUDENTS IN ZAMBOANGA SIBUGAY PHILIPPINES - Karen Benitez (Paedagogia: Jurnal Pendidikan, 2022)
In a Social Studies, students' academic motivation and attitudes will be useful to their academic progress. If a student is enthusiastic about a subject, he or she will do better in class and learn faster. There have been a lot of studies that have looked into students' academic motivation and attitudes toward social studies, but there does not appear to be any study that focuses on the learners themselves. This quantitative study aims to determine the level of academic motivation as well as the attitude toward social studies of 458 secondary students from public schools using the Academic Motivation Scale High School Version and Secondary Students Attitudes Towards Social Studies Scale. It also looked at whether there was a significant difference in academic motivation and attitude toward social studies when respondents were sorted by gender. Finally, it investigates the link between academic motivation and attitude towards social studies. Students are found to be "highly motivated" in terms of academic motivation and have a “positive attitude” toward social studies, according to the findings. Furthermore, when respondents were divided into gender groups, no significant differences in academic motivation and attitude toward social studies were found. Finally, academic motivation and attitude toward social studies show a significant favorable relationship.